KEMENANGAN KOTAK KOSONG DALAM PEMILIHAN BUPATI DAN WAKIL BUPATI PATI TAHUN 2017 - Aluisia Prita Parahita; Nur Hidayat Sardini; Priyatno Harsasto (Journal of Politic and Government Studies, 2018)
Pati local elections in 2017 which only included one single candidate leaving an interesting political phenomenon. Of the 101 regions in Indonesia that conduct head local election (PILKADA), there are only 9 regions whose Pilkada consists of single candidates, one of them is Pati. In Pati,